МЕТОДОЛОГИЯ ПРОГРАММИРОВАНИЯ УПРАВЛЕНИЯ ДАТЧИКОМ ДВИЖЕНИЯ НА ARDUINO UNO - Zoirov Sanjaridin Xolmuminovich; Xoshimov Temur Fakhriddin o‘g‘li; Boynazarova Nasiba Saydulla qizi; Sirojiddinov Shohijahon Husanboy o‘g‘li, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this work, the methodology of introducing modern information technologies of electronic sciences was considered using programs such as Multisim, Proteus, EdrawMax, PheT and LabVIEW. The principle of operation of Arduino UNO and its programming and computer processes were considered. Processes of motion sensor assembly and control using Arduino UNO were reviewed.